Confined optical modes and amplified spontaneous emission from a microtube cavity formed by vacumm assisted filtration - GOUNKO, IOURI; DONEGAN, JOHN FRANCIS; PEROVA, TANIA; RAKOVICH, YURY (American Physical Society, 2006)
The authors demonstrate a new route to the fabrication of individual aluminosilicate microtubes that can act as micron-scale optical cylindrical resonators. The microtubes were prepared using a simple vacuum assisted wetting and filtration through a microchannel glass matrix. Microphotoluminescence spectra of the microtube cavity show sharp resonant modes with quality factors up to 3200. A strong reduction of the emission decay time at high excitation power confirms the occurrence of amplified spontaneous emission from a single microtube.
PUBLISHED
Keywords: Physics